2019
DOI: 10.4102/abc.v49i1.2386
|View full text |Cite
|
Sign up to set email alerts
|

The alpine flora on inselberg summits in the Maloti–Drakensberg Park, KwaZulu-Natal, South Africa

Abstract: Background: Inselberg summits adjacent to the Maloti–Drakensberg escarpment occupy an alpine zone within the Drakensberg Alpine Centre (DAC). Inselbergs, the escarpment and surrounding mountains such as Platberg experience a severe climate; inselberg summits are distinct by being protected from human disturbance.Objectives: The aim of this article was to describe for the first time the flora of inselberg summits and to assess their potential contribution to conservation of DAC plant diversity.Method: We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…The present study observed a monotonic increase of narrow-endemic species with elevation, while as broad and non-endemic species decreased. A similar trend was observed by other researchers as well (Trigas et al 2013;Mráz et al 2016;Steinbauer et al 2016;Brand et al 2019). This pattern could be explained by two processes.…”
Section: Patterns Of Endemism Along Elevationsupporting
confidence: 91%
See 3 more Smart Citations
“…The present study observed a monotonic increase of narrow-endemic species with elevation, while as broad and non-endemic species decreased. A similar trend was observed by other researchers as well (Trigas et al 2013;Mráz et al 2016;Steinbauer et al 2016;Brand et al 2019). This pattern could be explained by two processes.…”
Section: Patterns Of Endemism Along Elevationsupporting
confidence: 91%
“…The present study observed a relatively disproportional dominance of species belonging to few families in the summit flora, rather than having a fair share of representation by many families. In this study, Asteraceae, Lamiaceae, and Ranunculaceae were the most dominant families, which go in line with the results of floristic studies in the same region (Dhar and Kachroo 1983;Dvorský et al 2011) or elsewhere (Rundel 2011;Shaheen et al 2015;Brand et al 2019). Since alpine regions possess extreme environmental conditions and high habitat heterogeneity (Körner 2016), it is likely that the plant species belonging to these families as adapted to a wide range of environmental conditions.…”
Section: Patterns Of Floristic Diversitysupporting
confidence: 88%
See 2 more Smart Citations
“… Carbutt’s (2019) Drakensberg Mountain Centre of Floristic Diversity and Endemism ( DMC ) includes the only alpine region in mainland Africa south of Mount Kilimanjaro ( Killick 1978 ), with a 2900 km disjunction. The DMC , covering some 40,000 km 2 , comprises a montane sub-centre, dominated by C 4 grass species and an alpine sub-centre [the former Drakensberg Alpine Centre of van Wyk and Smith (2001) and Carbutt and Edwards (2004 , 2006 )] dominated by C 3 grass species ( Brand et al 2019 ). The DMC is renowned for its high levels of plant diversity and endemism, hosting 227 endemic angiosperm species that account for ca.…”
Section: Introductionmentioning
confidence: 99%